(Dis)advantages of student subjects: what is your research question? - Simon Gächter (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2010)
In this comment on Henrich et al. (2010) I argue that the right choice of subject pool is intimately linked to the research question. At least within economics, students are often the perfect subject pool for answering some fundamental research questions. Student subject pools can provide an invaluable benchmark for investigating generalizability across different social groups or cultures.
Keywords: 330